FREEZING CHARACTERISTICS OF TROPICAL FISHES II.TILAPIA (Tilapia mosambica) - SHENOY, A VASANTHA; JAMES, M ARUL (Fishery Technology, 2025)
Tilapia from fresh water and brackish water-sources behaveddifferently during iced and frozen storage. The former showedan ice storage shelf life of about 13 days while the lattershowed signs of spoilage beyond 10 days. In their respectivefreezing characteristics, the samples from the two sources exhibitedfar more significant variations. The fresh water type iced for13 days preserved well for over 24 weeks when frozen and keptat a temperature of -18Â° C, while the brackish water variety heldin ice for lO days and subsequently frozen gave a shelf life ofonly 8 weeks under similar conditions.